INVESTIGATING EFL STUDENTS’ PERCEPTION AND PRACTICE OF ONLINE PEER ASSESSMENT IN THE SCHOOL CONTEXT - Siti Zulaiha; Rumiyati Rumiyati (Indonesian EFL Journal, 2024)
Recently, there has been an enhancement in the utilization of online peer assessment in the classroom and other language learning settings. This mixed-method study investigated EFL students' perceptions and practices of implementing online peer assessment. 66 senior and junior high school students were asked to fill out the closed-ended questionnaire and 15 students consented to fill the open-ended questionnaire. The survey data were analyzed using the Rasch Rating Scale Model with the assistance of Winsteps software; while the open-ended questionnaires were analyzed using thematic analysis. Results indicated that students showed positive and negative attitudes on practicing online peer assessment, perceived fairness of peer comments, and described personal learning experiences. Besides, in perceiving affective feedback, students showed a positive attitude toward online peer assessment; meanwhile, they had a negative attitude toward the system as they faced difficulty dealing with technical problems. These findings provide significant evidence of how the EFL students perceived the implementation of online peer assessment in the learning process.Keywords: Assessment; online peer assessment, students’ perception, EFL students.